The Effects of Iron Oxide Nanoparticle on Differentiation of Human Mesenchymal Stem Cells to Osteoblast - Tahereh Foroutan; Mohamad Zaman Kasaie (Negah Institute for Scientific Communication, 2015)
Introduction: IIron oxide nanoparticles (IO NP) have an increasing number of biomedical applications. To date, the potential cytotoxicity of these particles remains an issue of debate. Little is known about the cellular interaction or toxic effects of IO NP on differentiation of stem cells. The aim of the present study was to investigate the possible toxic role of different doses of IO NP in differentiation of human mesenchymal stem cells (hMSCs) derived bone marrow to osteoblast. Methods: hMSCs were seeded on normal stem cell medium with added 20 and 70µg/ml of IO NPs. Post confluence (2 weeks), cells growing cell viability was measured by 3-(4, 5-Dimethylthiazol-2-yl) -2, 5 -diphenyltetrazolium bromide (MTT) assays. hMSCs at passage 2 were cultured in osteogenic medium added with 20 and 70 µg/ml of IO NPs. The expression of osteogenesis markers of osteopontin, osteocalcine in different groups was compared by RT-PCR assay. Results: Our findings showed that cell viability of hMSCs cultured in normal stem cell media containing 20µg/ml IO NPs was significantly (P>0.05) lower than control and 70µg/ml dose of IO NPs groups, while there was no significant difference between control and 70µg/ml dose of IO NP. The expression level of osteoblast markers osteopontin and osteocalcin in hMSCs differentiated to osteoblast in dose with 20µg/ml IO NPs was significantly lower than the other groups, while the expression level of osteopontin and osteocalcin in 70µg/ml IO NPs dose was insignificantly higher than control group. Conclusion: To summarize, the presence of IO NPs with low dose influenced the cell viability cells in normal stem cell media, demonstrating toxicity of this material with 20µg/ml. It could be probably due to penetrating particles throughout cell membrane. This represents a critical aspect to its successful use for stem cell-based regenerative medicine strategies.